New Approach to Metal Biomarker Detection Using Nonionizing Electromagnetic Field - Radil, Roman; Barabas, Jan; Kamencay, Patrik (Communications - Scientific Letters of the University of Zilina, 2015)
Medical detection techniques used for preoperative scanning of certain marked areas are mostly based on ionizing radiation as it is in case of CT. This paper provides an unusual approach to detection of metal biomarkers implanted into the human body, based on nonionizing radiation and discusses problems and complications connected with chosen technique.
Keywords: non-destructive evaluation; eddy current testing; metal biomarker detection; modeling and numerical simulation